Neutrophil elastase levels in the gingival crevicular fluid following hyaluronan gel application in the treatment of chronic periodontitis: A randomized split-mouth study - Savita Mallikarjun; Abhilash Neelakanti; Harsha Mysore Babu; Sujatha Ballambettu Pai; Sachin Vaijnathrao Shinde; Swathi Krishnan (Wolters Kluwer Medknow Publications, 2016)
Background: Neutrophils are the predominant leukocytes in the periodontium, which prevent infection from periodontal pathogens and subsequent tissue destruction. A potentially destructive role has been elucidated, especially due to elastase enzyme. Controlling its levels might be crucial in minimizing the tissue destruction. Hyaluronan, known to inhibit the release of this enzyme from neutrophils, might be a viable option to treat chronic periodontitis. Aims: The aim of this study is to evaluate and compare the effects of 0.2% hyaluronan gel adjunctive to scaling and root planing on the levels of elastase in gingival crevicular fluid (GCF). Settings and Design: This split-mouth study included eighty (forty experimental and forty control) sites from twenty patients representing both sexes. Materials and Methods: GCF samples were collected from all the eighty sites; simultaneously, clinical periodontal parameters were recorded. Enzyme-linked immunosorbent assay was used to determine the levels of elastase at baseline and 6 weeks after therapy, following mechanical debridement and subsequent subgingival placement of the experimental drug. Statistical Analysis Used: With the aid of statistical software (SPSS Version 13), Student's t-test and Pearson's correlation test were performed. Results: There was a mean reduction in the elastase levels from baseline to 6 weeks after therapy in the experimental group. However, the difference between the groups was not statistically significant. Conclusions: Adjunctive use of hyaluronan following mechanical debridement resulted in comparable reduction in the elastase levels, suggesting that this substance has an inhibitory effect on elastase, and subsequent tissue destruction. Further long-term studies are mandatory to validate the results of this study.